PENGARUH GAYA EVALUASI ATASAN TERHADAP TEKANAN DAN KEPUASAN KERJA BAWAHAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIBEL MODERATING - Aida Nahar (Jurnal Dinamika Ekonomi & Bisnis, 2004)
AbstractMost of accounting studies had examined the relationship between the evaluative style of superiors and work related attitudes of subordinates. The result, however, showed that relationships were not consistent. These conflicting evidence reflected the influence of conti11ge11cy variables in the effect the relationship between the evaluative style of superiors and work related attitudes of subordinates. This paper extends previous work in the area of supervisory style as it pertains to the use of budgetary information for performance evaluation. This study examined influence of the evaluative style of superiors on job related tension and job·satisfaction with organization's culture as moderate variables. This study focused exclusively on the superior's budgetary pe1formance evaluation style a11d used multiple regression's model.Based  on the fifty  production  and marketing managers questionair  respon of a number ofmanufacturing companies in Central Java, the results of the  study, showed that budgetary performance evaluation style in the  organization's culture that job oriented, made high job related  tension and low job  satisfaction  of subordinates. Keywords: Budgetary  pe1formance  evaluation  style,  Job  related  tension,  Job  Satisfaction 01 ganization s culture